Functional Ultrastructure of the Excretory Gland Cell in Zoonotic Anisakids (Anisakidae, Nematoda) - Ivona Mladineo; Jerko Hrabar; Hrvoje Smodlaka; Lauren Palmer; Kristen Sakamaki; Kleoniki Keklikoglou; Pantelis Katharios (Cells, 2019)
Excretory and secretory products are crucial for parasite infectivity and host immunomodulation, but the functioning and ultrastructure of the excretory gland cell (EC) that produces these products are still scarcely understood and described. In light of growing reports on anisakiasis cases in Europe, we aimed to characterise the EC of larval Anisakis pegreffii and adult Pseudoterranova azarasi. In the latter, EC starts 0.85 mm from the head tip, measuring 1.936 × 0.564 mm. Larval EC shows a long nucleus with thorn-like extravaginations toward the cytoplasm, numerous electron-dense and -lucent secretory granules spanning from the perinuclear to subplasmalemmal space, an elevated number of free ribosomes, small, spherical mitochondria with few cristae and a laminated matrix, small and few Golgi apparatuses, and few endoplasmic reticula, with wide cisternae complexes. Ultrastructure suggests that anaerobic glycolysis is the main metabolic pathway, obtained through nutrient endocytosis across the pseudocoelomic surface of the EC plasmalemma and its endocytic canaliculi. Thorn-like extravaginations of EC karyotheca likely mediate specific processes (Ca2+ signaling, gene expression, transport, nuclear lipid metabolism) into the extremely wide EC cytosol, enabling focal delivery of a signal to specific sites in a short time. These functional annotations of parasitic EC should help to clarify anisakiasis pathogenesis.